Connections : brain, mind, and culture in a social anthropology - Reyna, Stephen P. (Routledge, 2002)
Have you ever wondered how the internal space of our brain connects with the external space of society? Drawing on hermeneutics and neuroscience Stephen Reyna develops an anthropological theory that explains the relationship between the biological and the cultural. Recent popular interest in the brain is evident, and now social anthropologists are starting to consider connections between science and anthropology. Reyna is an anthropologist prepared to tackle big and difficult questions. This accessibly written book will cause quite a stir in anthropology, and will appeal to those interested.